Child Labor Among Syrian Refugees in Turkey - Fehr, Irina; Rijken, Conny (Frontiers in Human Dynamics, 2022)
Nearly 4 million Syrian refugees, including more than 1.8 million Syrian children, fled to Turkey during the Syrian war, where they face many challenges to rebuild their lives. They are confronted with restrictions on their residence status and access to the labor market, limiting their formal employment opportunities. Poverty and labor exploitation are widespread consequences, and to make ends meet, children are driven into the workforce. In Turkey, child labor among Turkish nationals is also widespread as follows from the Turkish national child labor survey from 2019, creating a fertile ground for Syrian children to take up work. Although child labor among the Syrian refugee population is gaining increasing attention among scholars and humanitarian actors, knowledge about its extent or characteristics remains limited. Drawing on a survey conducted in late 2020, this paper contributes to a deeper and more numerically based understanding of the current situation of Syrian minor workers in Turkey. The quantitative results of our research are compared with the Turkish national child labor survey, highlighting the differences and commonalities between Syrian and Turkish children working in the country and looking into the impact of the lack of permanent residency on the prevalence of child labor. Our findings suggest that Syrian children enter the labor force at a younger age and have less access to education while working very long hours and earning low wages. The study thus demonstrates the specific vulnerabilities of Syrian children to labor exploitation.